Agriculture and its development in Basra District through reports of the Administrative Inspector For the period 1945-1958 - Silawi Lafta, Lect .Dr. Hamid; Abdel Sattar Katea, Lect .Dr. Ahmed (Basra studies journal, 2024)
The Basra District witnessed a remarkable development in traditional economic activity, especially the agricultural sector, which was practiced by many of the people of the District. This was helped by the nature of agricultural lands and the availability of water, which led to the prosperity of palm cultivation, which spread in various areas of the District. Palm cultivation helped in the emergence of a number of The industries that were associated with it, including the date pressing industry, as these presses spread, were not all owned by the people in the palm growing areas, and agriculture constituted an important resource for the Iraqi treasury for the district. However, these economic activities were not without some problems, which were proven by government reports regarding the flood. Agriculture was greatly affected, including problems between the farmer and the landowners. The animal revolution had a limited impact on the development of the agricultural economy, due to the spread of infectious diseases among animals, as well as the weakness of the veterinary staff in treating diseases. The Agricultural Bank had a major impact in supporting the farmer by giving advances. For land-owning farmers, which led to the development of the agricultural sector and contributed to the economic development of Iraq in general and the Basra District in particular.